2015
DOI: 10.1073/pnas.1412165112
|View full text |Cite
|
Sign up to set email alerts
|

Highly polarized C-terminal transition state of the leucine-rich repeat domain of PP32 is governed by local stability

Abstract: The leucine-rich repeat domain of PP32 is composed of five β-strand-containing repeats anchored by terminal caps. These repeats differ in sequence but are similar in structure, providing a means to connect topology, sequence, and folding pathway selection. Through kinetic studies of PP32, we find folding to be ratelimited by the formation of an on-pathway intermediate. Destabilizing core substitutions reveal a transition state ensemble that is highly polarized toward the C-terminal repeat and cap. To determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 67 publications
(92 reference statements)
7
36
2
Order By: Relevance
“…S2 E-J, S3 E-J, and S4 E-J and Table S1), indicating that all residues reflect the complete transition from the folded to the unfolded state. The average ΔG f values are in good agreement with the values obtained for these variants previously from CD-detected urea unfolding (Table 1) (21). The volume changes for these variants are much larger (by 59-72 mL/mol) than that obtained previously for WT pp32 (Table 1 and SI Appendix, Fig.…”
Section: Cavity Creation Causes Context-dependent Chemical Shift Pertsupporting
confidence: 89%
See 2 more Smart Citations
“…S2 E-J, S3 E-J, and S4 E-J and Table S1), indicating that all residues reflect the complete transition from the folded to the unfolded state. The average ΔG f values are in good agreement with the values obtained for these variants previously from CD-detected urea unfolding (Table 1) (21). The volume changes for these variants are much larger (by 59-72 mL/mol) than that obtained previously for WT pp32 (Table 1 and SI Appendix, Fig.…”
Section: Cavity Creation Causes Context-dependent Chemical Shift Pertsupporting
confidence: 89%
“…1). The global stability and folding mechanism of WT pp32 have been well characterized (21,22). The ϕ-value analysis revealed an early transition state in which the C-terminal capping motif and the fifth repeat are ordered at the folding barrier.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The repeat units are individually cooperative, have low stability, and are further stabilized by their interfacial interactions. Repeat proteins have been found to fold in repeatsized steps, one or several units at a time, in a distinct pathway order (66,67)…”
Section: Results and Considerationsmentioning
confidence: 99%
“…It was of great interest to us that a kinetic study 27 has shown that LRRCT is an essential core domain required for proper folding of the LRR protein PP32. Since the replacement of the first tyrosine or the fifth valine of the LRRCT consensus sequence affects the folding of LRR protein, 10,27 missense mutations in these amino acids were expected to decrease the levels of functional protein. We preferentially studied the compound heterozygous mutations to confirm the mutation impacts on both Y107 and V111.…”
Section: Discussionmentioning
confidence: 99%